EVALUATION OF THE ACUTE TOXICITY OF LIANA BARK OF LANDOLPHIA OWARIENSIS P. BEAUV. (APOCYNACEAE) - Ismael, Dally Laba; Yaya, Fofana; Claude, Kablan Ahmont Landry; José, Lia Arthur (International Journal of Research -GRANTHAALAYAH, 2020)
The objective of this study was to assess the acute toxicity of the decocted bark of the liana bark of L. owriensis P. Beauv. (Apocynaceae) in the Wistar strain rat. The study of acute toxicity was carried out according to the OECD 423 method. This study was carried out up to a limit dose of 5000 mg / kg of body weight. After administration of different oral doses, observations on behavior, respiration, skin effects, response of the sensory nervous system or the gastrointestinal effects of animals were made on the 1st, 2nd, 3rd and 14 days (OECD 423). During 14 days of observation, a decoction of the bark of liana from L. owriensis did not show any mortality or lead to obvious toxicity on the mice at the respective doses of 300, 2000 and 5000 mg / kg. The decoction is not toxic to rats, even in large doses (5000 mg / kg of body weight). Therefore, the vine barks of this plant could be used for effective therapeutic purposes.